Two New Distributional Records in Genus Sida L. to the Flora of Maharashtra State, India - Govekar, R. S.; Kamble, T. D.; Tambde, G. M.; Nimbalkar, V. V.; Sardesai, M. M. (Journal of the Bombay Natural History Society (JBNHS), 2019)
No Abstract.